2005
DOI: 10.1007/s00216-005-0063-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of magnesium, calcium, sodium, and potassium in blood plasma samples by capillary zone electrophoresis

Abstract: A capillary zone electrophoretic assay has been developed and validated for analysis of magnesium, calcium, sodium, and potassium in blood plasma samples. Optimum results were obtained with 20 mmol L(-1) imidazole (pH 2.8) and 0.5 mmol L(-1) oxalic acid containing 5% methanol, capillary temperature 25 degrees C, applied voltage 30 kV, hydrodynamic injection time 3 s, and a poly(vinyl alcohol)-coated capillary (i.d. 50 microm, total length 64.5 cm and effective length 56 cm). Indirect detection was performed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…This eliminates the detrimental effect of the sample matrix and improves the detection sensitivity of the analytical system and can be achieved using conventional extraction techniques, such as liquid-liquid extraction [2] and solid-phase extraction [3]. Precipitation with a suitable agent followed by centrifugation can also be used to remove proteins and cellular matter [4]. However, these procedures are time consuming, costly, require large sample volumes and necessitate use of organic solvents and of extra, often cumbersome instrumentation.…”
Section: Introductionmentioning
confidence: 97%
“…This eliminates the detrimental effect of the sample matrix and improves the detection sensitivity of the analytical system and can be achieved using conventional extraction techniques, such as liquid-liquid extraction [2] and solid-phase extraction [3]. Precipitation with a suitable agent followed by centrifugation can also be used to remove proteins and cellular matter [4]. However, these procedures are time consuming, costly, require large sample volumes and necessitate use of organic solvents and of extra, often cumbersome instrumentation.…”
Section: Introductionmentioning
confidence: 97%
“…Many speciation analyses were carried out by CE inductively coupled plasma atomic emission spectrometry (ICP-AES) and other hyphenated techniques [27][28][29][30][31][32]. Also, capillary electrophoretic analyses of cations in plasma have been reported in literatures [33][34][35], for example, there were several reports for determination of free magnesium or calcium ions concentrations [36][37][38][39]. Painter and Wang [40] used a new zymosan-conjugated chloride probe for measurement of free chloride level within phagolysosomes of neutrophils and other phagocytic cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Impurity (and purity) analysis of drugs [18,59], preparations [146], and tablets [102,[147][148][149] have also been demonstrated with MEKC. Other reports have demonstrated means of determining metabolites [60,68,81,117,125], degradation products [92] and constituent analysis [65,94,150,151]. Drug enantiomers are a pervading topic in pharmaceutical research, and MEKC separations of drug enantiomers have been demonstrated during the time frame of this review [48,59,60,62,65,144].…”
Section: Pharmaceuticalsmentioning
confidence: 95%